COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) METHOD TO READING COMPREHENSION ON DESCRIPTIVE TEXT OF EIGHT GRADERS AT SMPN 5 TAKENGON, ACEH TENGAH - Cut Dara Ilfa Rahila; Rini Fitria (Politeknik Negeri Bengkalis, 2020)
Reading is one of receptive skills which lead people learn the context from kinds of information. The readers should be able to find out the main information from the text cearly. In this study, the researcher focused on studentsâ€™ comprehension skill on reading descriptive text. Having done a pre-research, it was found that there were many students found it difficult to find out specific information from the text they read. Due to the finding, the research was aimed at finding out whether Cooperative Integrated Reading and Composition (CIRC) method was effective to improve students reading comprehension on descriptive text to second graders at SMPN 5 Takengon. Methodologically, this research referred to quantitative approach with experimental research design. The population of this research was all of the eight grade students of SMP N 5 Takengon with total number 112 students. As many 80 students were chosen to be samples which were divided into two classes, experimental and control, 40 students in each class. The data were analyzed by using t-test. It was found that the value of tobtainedÂ is higher than ttable (6.66 > 2.02) at the level of significance 0,05. Meaning, Cooperative Integrated Reading and Composition (CIRC) method affected studentsâ€™ reading comprehension ability on descriptive text.